2014
DOI: 10.1249/mss.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Muscle Cooling Enhances Gene Expression of PGC-1α

Abstract: These data indicate that an acute postexercise cooling intervention enhances the gene expression of PGC-1α and may therefore provide a valuable strategy to enhance exercise-induced mitochondrial biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 44 publications
6
78
1
Order By: Relevance
“…For instance, in studies using cell culture and animal models, mitochondrial biogenesis has shown to be up-regulated following both heat and cold exposures through PGC-1α dependant mechanisms similar to that observed following exercise (Bruton et al, 2010;Liu & Brooks, 2012;Puigserver et al, 1998;Tamura et al, 2014;Wu et al, 1999). However, when administered following exercise, both heat and cold interventions have demonstrated contradictory results, with some studies showing beneficial, while others detrimental effects on PGC-1α and/or muscle aerobic performance (Ihsan et al, 2014;Slivka et al, 2013;Slivka et al, 2012;Tamura et al, 2014;Yamane et al, 2006). Taken together, these studies highlight the potential of these modalities to both enhance and diminish mitochondrial adaptations to training, as well implicating PGC-1α as a key target in these mechanisms.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…For instance, in studies using cell culture and animal models, mitochondrial biogenesis has shown to be up-regulated following both heat and cold exposures through PGC-1α dependant mechanisms similar to that observed following exercise (Bruton et al, 2010;Liu & Brooks, 2012;Puigserver et al, 1998;Tamura et al, 2014;Wu et al, 1999). However, when administered following exercise, both heat and cold interventions have demonstrated contradictory results, with some studies showing beneficial, while others detrimental effects on PGC-1α and/or muscle aerobic performance (Ihsan et al, 2014;Slivka et al, 2013;Slivka et al, 2012;Tamura et al, 2014;Yamane et al, 2006). Taken together, these studies highlight the potential of these modalities to both enhance and diminish mitochondrial adaptations to training, as well implicating PGC-1α as a key target in these mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…As such, it is not possible in these studies to determine if differences in cell signalling were temperature or contraction driven. Nevertheless, recent study by Ihsan et al (2014) has demonstrated that cold-induced shivering thermogenesis was not necessary to enhance aerobic adaptations mediated by exercise. Indeed, using a one-legged cooling design to avoid shivering, Ihsan et al (2014) showed that 15 min of postexercise cold water immersion (10°C) resulted in increased mRNA content of PGC-1α following exercise.…”
Section: Post-exercise Cold Exposurementioning
confidence: 98%
See 3 more Smart Citations